2000
DOI: 10.2174/1389450003349290
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Proteinases of Trypanosome Parasites Novel Targets for Chemotherapy

Abstract: The protozoan parasites, Trypanosoma brucei and T. cruzi, that cause sleeping sickness in sub-Saharan Africa and Chagas' Disease in Latin America, respectively, exert significant morbidity and mortality in man. Combinations of toxicity and differential efficacy of current drugs provide an urgent need to develop novel, cheap and effective chemotherapies. Research over the last decade with cultured trypanosomes and mice experimentally infected with these parasites has demonstrated that trypanosome cysteine prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 0 publications
0
68
0
7
Order By: Relevance
“…Both in vitro and in vivo studies have shown that cysteine protease activity is required for T. brucei survival (5,6,29,30). RNAi studies implicated tbcatB as an essential protease (4).…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies have shown that cysteine protease activity is required for T. brucei survival (5,6,29,30). RNAi studies implicated tbcatB as an essential protease (4).…”
Section: Discussionmentioning
confidence: 99%
“…infections (91), could also be involved in AT-induced immune depression, anemia, thrombocytopenia, or central nervous system (CNS) invasion (7,8,42,63,111,152). In addition, CPs are considered potential targets for future drug design (trypanocide and antidisease) as well as antidisease vaccine candidates (29,64,92). Although most of the literature has dealt with T. cruzi CP (cruzain or cruzipain), CPs from T. brucei brucei, T. congolense, and T. brucei rhodesiense have also been extensively studied (8,28,42,56,67,90,119,134,152).…”
Section: The Major Candidatesmentioning
confidence: 99%
“…In this regard, biochemical pathways general to parasites but absent from mammalian hosts have long been an attractive source of molecular targets for anti-infective drug development [23,27]. Additionally, biochemical peculiarities of the parasites such as (i) turnover rates [42,43]; (ii) structure of biological membranes [44][45][46][47]; (iii) cell signaling [48] and (iv) protein expression and regulation [49] have also been investigated as potential targets for drug intervention [50].…”
Section: Molecular Targets For Drug Designmentioning
confidence: 99%